2019
DOI: 10.1111/vsu.13268
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a continuous epitendinous suture as adjunct to three‐loop pulley and locking‐loop patterns for flexor tendon repair in a canine model

Abstract: Objective To evaluate the effect of combining a continuous epitendinous suture with three‐loop pulley (3LP) and locking‐loop (LL) core patterns for flexor tendon repair. Study design Ex vivo biomechanical study. Sample population Seventy‐two cadaveric superficial digital flexor musculotendon (SDFT) units. Methods Tendons were divided into four groups (n = 18/group). After sharp transection, SDFT were repaired with 3LP, LL, 3LP + epitendinous (E), or LL + E suture patterns. After preloading, repaired constructs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
84
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 32 publications
(93 citation statements)
references
References 35 publications
(89 reference statements)
8
84
1
Order By: Relevance
“…13,17 One study showed that the addition of a continuous epitendinous suture pattern to the 3LP and LL suture patterns eliminated small gaps between the tendon ends and increased failure loads of both repair methods more than twofold. 16 To our knowledge, those techniques have not been used in cases with a wide, non-reducible gap, such as the 7 mm gap in the present case. Further studies are required to determine healing times as well as acquisition of adequate strength of the AT repair in cases with a wide gap.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…13,17 One study showed that the addition of a continuous epitendinous suture pattern to the 3LP and LL suture patterns eliminated small gaps between the tendon ends and increased failure loads of both repair methods more than twofold. 16 To our knowledge, those techniques have not been used in cases with a wide, non-reducible gap, such as the 7 mm gap in the present case. Further studies are required to determine healing times as well as acquisition of adequate strength of the AT repair in cases with a wide gap.…”
Section: Discussionmentioning
confidence: 80%
“…5,7,13 The 3LP and the LL suture patterns have both been advocated for the repair of transected round or semiround tendons in dogs. 7,13,16,17 In one study, a modified 3LP suture pattern was found to be superior to the LL technique for reattaching canine tendon to bone and for reducing gap formation. 13 Barbed polypropylene suture material did not appear to provide a major benefit when used in a modified 3LP suture pattern.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations